2015
DOI: 10.1080/00223891.2015.1039015
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Narcissistic Personality Inventory With Binary and Rating Scale Items

Abstract: Narcissistic Personality Inventory (NPI) items typically have a forced-choice format, comprising a narcissistic and a nonnarcissistic statement. Recently, some have presented the narcissistic statements and asked individuals to either indicate whether they agree or disagree that the statements are self-descriptive (i.e., a binary response format) or to rate the extent to which they agree or disagree that these statements are self-descriptive on a Likert scale (i.e., a rating response format). The current resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 69 publications
(156 reference statements)
0
22
0
Order By: Relevance
“…It is possible that the psychometric properties of the NPI would be clarified if the 40 couplets were rated as individual items. In fact, multiple studies have applied the NPI in a single-stimulus format (Bogart, Benotsch, & Pavlovic, 2004;Boldero, Bell, & Davies, 2015;R. P. Brown & Zeigler-Hill, 2004;Egan & Lewis, 2011;Gerbasi & Prentice, 2013;Jordan, Spencer, Zanna, Hoshino-Browne, & Correll, 2003;Lee, Gregg, & Park, 2013;Morf & Rhodewalt, 1993), although these investigations did not check whether equivalent constructs were measured across formats.…”
Section: ) Dimensionality and Factorial Structurementioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the psychometric properties of the NPI would be clarified if the 40 couplets were rated as individual items. In fact, multiple studies have applied the NPI in a single-stimulus format (Bogart, Benotsch, & Pavlovic, 2004;Boldero, Bell, & Davies, 2015;R. P. Brown & Zeigler-Hill, 2004;Egan & Lewis, 2011;Gerbasi & Prentice, 2013;Jordan, Spencer, Zanna, Hoshino-Browne, & Correll, 2003;Lee, Gregg, & Park, 2013;Morf & Rhodewalt, 1993), although these investigations did not check whether equivalent constructs were measured across formats.…”
Section: ) Dimensionality and Factorial Structurementioning
confidence: 99%
“…Small to moderate correlations between socioeconomic status and NPI scores were also found in our study for the total score and the leadership and vanity facets (e.g., latent r = .22 for total NPI) in the unidimensional forced-choice format. For data based on the multidimensional forced-choice format and the true/false and rating scale format, socioeconomic status was positively related Future research could also investigate the incremental validity of one facet over the others or investigate in how far the specific facets predict criteria over and above a shared narcissism dimension in the context of a bifactor model (see for example Boldero et al, 2015).…”
Section: Relationships Between Npi Facets and Other Variablesmentioning
confidence: 99%
“…According to Barelds and Dijkstra (2010), the correlation between the dichotomous forced-choice format and a 5-point Likert version of the scale (using the dichotomous statements as anchor points) is excellent ( r = 0.97; p < 0.01). In Boldero et al (2015) the use of a 6-point rating scale showed a similar correlation ( r = 0.96; p < 0.01).…”
Section: Introductionmentioning
confidence: 61%
“…Kubarych et al (2004) proposed a 2-factor or a 3-factor model with (1) Power and (2) Exhibitionism as the two factors of the first one, and (1) Power, (2) Exhibitionism, and (3) Being a Special Person as the three factors of the second one. Inconsistent results in factor structure are generally considered to be associated with methodological differences between studies (see in Boldero et al, 2015). However, even the most recent studies that have taken the current psychometric recommendations into account (performing tetrachoric correlation matrix because of the dichotomous format, using the scree plot and interpreting the items' meanings to obtain a factor solution, …), failed to replicate the 7-factor structure (Corry et al, 2008; Ackerman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation